Conceptual foundations of information security of national economy in the conditions of digitalization - Onyshchenko, Svitlana; Hlushko, Alina (Social Economics, 2020)
The article focuses on defining the conceptual foundations of information security of the national economy in terms digitalization. The study revealed the dual relationship between the processes Djilas and the development of the economic system, actualized the problem of information security in today’s economy. Based on the analysis of the chronology of major cyber-attacks on information systems, the level and dynamics of cyber-attacks and cybercrime, the financial losses of the national economy from cybercrime the need for information security was justified. The conceptual-categorical basis of information security of the national economy was formed. The links between the basic categories of development of digitalization processes, management of the national economy and provision of information security were determined. Based on the analysis of the scientific literature, three main conceptual approaches to defining the essence of information security were defined, in accordance with which information security is considered as a component of national security; the protection of the information environment and national interests from possible threats; the state of the system, which is able to ensure appropriate security settings. The content of the notion ‘information security of the national economy’ was extended and defined as a condition of protection of the information environment, ensuring the realization of national economic interests, the stability of the national economy to both internal and external, real and potential threats associated with the rapid development of digitalization. The structural model of information security of the national economy was developed, based on systemic and protective approaches, its properties and interrelation of elements with external environment were defined. It was proved that the protection of national economic interests is the basis of the information security of the national economy. The proposed system of information security of the national economy has identified a legitimate basis for further study of the priority directions of ensuring information security in terms of digitalization.